Ethnophysics Study of Sound Waves from Process Making Putu Cake as a Medium Physics Learning - Arita Fajar Damasari; Eka Sofiyanti; Eka Krisna Samudra; Vira Safitri; Subiki Subiki (Berkala Ilmiah Pendidikan Fisika, 2022)
Putu cake is a traditional snack that is rarely liked by the public. One uniqueness of the putu cake is the sound of the steam produced. Making putu cake can be related to the concept of physics. This study aims to examine the concept of sound waves in the process of making putu cakes for physics learning media. This study uses a qualitative method with an ethnographic approach. Sources of data were obtained through interviews and observations. The collected data is then analyzed and presented as descriptive text. The results obtained are that the larger the mass of the putu cake, the smaller the frequency and amplitude, according to Marsenne's Law. The frequency value is directly proportional to the amplitude but inversely proportional to the surface area. In making putu cake, humans can hear frequencies ranging from 1,400 Hz to 1,800 Hz. The concept of physics in the process of making putu cakes can be used as a physics learning media for sound wave material that is useful for teachers